Commercial complementary food consumption is prospectively associated with added sugar intake in childhood - Foterek, Kristina; Buyken, Anette; Bolzenius, Katja; Hilbig, Annett; Nöthlings, Ute; Alexy, Ute (British Journal of Nutrition)
Abstract Given that commercial complementary food (CF) can contain high levels of added sugar, a high consumption may predispose to a preference for sweet taste later in life. This study examined cross-sectional associations between commercial CF consumption and added sugar intake in infancy as well as its prospective relation to added sugar intake in pre-school and primary-school age children. In all, 288 children of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study with 3-d weighed dietary records at 0·5 and 0·75 (infancy), 3 and 4 (pre-school age) and 6 and 7 years of age (primary-school age) were included in this analysis. Individual commercial CF consumption as percentage of total commercial CF (%cCF) was averaged at 0·5 and 0·75 years. Individual total added sugar intake (g/d, energy percentage/d) was averaged for all three age groups. Multivariable logistic and linear regression models were used to analyse associations between %cCF and added sugar intake. In infancy, a higher %cCF was associated with odds for high added sugar intake from CF and for high total added sugar intake (>75th percentile, P <0·033). Prospectively, a higher %cCF was related to higher added sugar intake in both pre-school ( P <0·041) and primary-school age children ( P <0·039), although these associations were attenuated in models adjusting for added sugar intake in infancy. A higher %cCF in infancy may predispose to higher added sugar intake in later childhood by virtue of its added sugar content. Therefore, offering home-made CF or carefully chosen commercial CF without added sugar might be one strategy to reduce sugar intake in infancy and later on.